2011
DOI: 10.1128/jvi.05565-11
|View full text |Cite
|
Sign up to set email alerts
|

A Multifunctional Protein Encoded by Turkey Herpesvirus Suppresses RNA Silencing in Nicotiana benthamiana

Abstract: Many plant and animal viruses counteract RNA silencing-mediated defense by encoding diverse RNA silencing suppressors. We characterized HVT063, a multifunctional protein encoded by turkey herpesvirus (HVT), as a silencing suppressor in coinfiltration assays with green fluorescent protein transgenic Nicotiana benthamiana line 16c. Our results indicated that HVT063 could strongly suppress both local and systemic RNA silencing induced by either sense RNA or double-stranded RNA (dsRNA). HVT063 could reverse local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…Our experimental data demonstrated that the predicted P. xylostella LINE VSR domain exhibits a weak, compared to the potent plant virus VSR p19, but detectable ability to suppress RNA silencing in the Nicotiana benthamiana leaves ( Lazareva et al, 2015 ). In this context, it is important that plant and insect VSRs can substitute for each other in different eukaryotic model systems ( Jing et al, 2011 ; Maliogka et al, 2012 ; Zhu et al, 2012 ). Moreover, the plant VSRs were shown to suppress retrotransposon silencing in heads and ovaries of insects by endogenous siRNAs ( Berry et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our experimental data demonstrated that the predicted P. xylostella LINE VSR domain exhibits a weak, compared to the potent plant virus VSR p19, but detectable ability to suppress RNA silencing in the Nicotiana benthamiana leaves ( Lazareva et al, 2015 ). In this context, it is important that plant and insect VSRs can substitute for each other in different eukaryotic model systems ( Jing et al, 2011 ; Maliogka et al, 2012 ; Zhu et al, 2012 ). Moreover, the plant VSRs were shown to suppress retrotransposon silencing in heads and ovaries of insects by endogenous siRNAs ( Berry et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…The key relevance of these proteins for the infection life cycle has been established in multiple virus/host combinations, showing that the absence of an active VSR results in greatly reduced viral infection [19,[20][21][22][23][24][25]. Interestingly, it has been found that several vertebrate-infecting viruses also encode proteins with the ability to counteract RNA silencing, such as NS1 from Influenza A virus [26][27][28][29], VP30, VP35 and VP40 from Ebola virus [28,30,31], NSs from La Crosse virus [32], s3 from Mammalian orthoreovirus type 3 [33], E3L from Vaccinia virus [28,29], Tas from Primate foamy virus type 1 [34], Tat from Human immunodeficiency virus [35], Rex from Human T-cell lymphotropic virus [36], C and E2 proteins from Hepatitis C virus [37][38][39], 7a from Severe acute respiratory syndrome virus [40], and HVT063 from Turkey herpesvirus [41], presumably as part of the attack-defense-counterdefense arms race between viruses and their hosts (some of these RSSs were recently reviewed [42,[43][44][45][46]).…”
Section: Introductionmentioning
confidence: 99%
“…The harvested leaves were used for total RNA isolation according to a previous study (Jing et al ). The cDNA was synthesized according to the standard procedures of the RevertAid Fist Strand cDNA Synthesis Kit (ThermoFisher, Waltham, MA).…”
Section: Methodsmentioning
confidence: 99%